1983
DOI: 10.1099/0022-1317-64-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Physical Maps of the DNAs of Two Cytomegalovirus Strains

Abstract: SUMMARYThe physical maps of the DNAs of two cytomegalovirus isolates, AD 169 and SG, were compared by cross-blot hybridization and by hybridization of nitrocellulose-bound SG fragments with cloned 32p_labelled AD 169 fragments. From this comparison it can be concluded that both physical maps are co-linear to a large extent. Most variability existed at the termini of the long and short component (at the repeats). Other differences were the presence or absence of restriction endonuclease cleavage sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…This is in line with the previous finding that the ends of the L and S components of HCMV tend to be deleted without affecting infectivity (Weststrate et al, 1983;Furukawa, 1984). The pathogenicity and genetics of HCMV strain Tanaka in connection with its peculiar genome structure will be the subjects of future studies.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with the previous finding that the ends of the L and S components of HCMV tend to be deleted without affecting infectivity (Weststrate et al, 1983;Furukawa, 1984). The pathogenicity and genetics of HCMV strain Tanaka in connection with its peculiar genome structure will be the subjects of future studies.…”
Section: Discussionsupporting
confidence: 87%
“…The genomes of human cytomegalovirus (HCMV) strains (defined in Table 1) are highly related as judged by reassociation kinetics [3,4] and Southern analyses [3,[5][6][7]. Different strains of HCMV, however, are readily distinguishable from one another by comparing patterns of restriction enzyme digested viral DNA.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION Analysis of the genomes of four strains of HCMV by DNA-DNA hybridization with cloned subgenomic fragments of strain AD169 has allowed us to ascertain that the genomes of these HCMV strains are colinear with that of AD169 used as a reference strain. This notion was first suggested by LeFemina & Hayward (1980) and later by Weststrate et al (1983). The latter authors compared the BglII, HindIII and XbaI maps of the AD169 and SG strains by crosshybridization.…”
Section: Hybridization With Xbai Digests Of Hcmv Dnamentioning
confidence: 87%
“…It has been suggested that some digestion fragments have the same size and map position in the UL and Us regions of the genome. LaFemina & Hayward (1980) and later Weststrate et al (1983) suggested that HCMV genomes might be colinear. There appear to be size differences in the repeat regions (Geelen & Weststrate, 1982;Tamashiro et al, 1984).…”
Section: Introductionmentioning
confidence: 99%